Meta-heurística baseada em simulated annealing para programação da produção em máquinas paralelas com diferentes datas de liberação e tempos de setup - (:unkn) unknown (Universidade Federal de Goiás, 2015)
This study deals with problems of parallel machines with independent setup times, different dates of release and minimizing the makespan. The production environment is common in the auto industry that there may be jobs through the production line, they are added new machines or equal equipment to expand productive capacity. Any production process requires effective management by the Production Planning and Control (PCP). This activity includes the planning of production, so the allocation of resources for task execution on a time basis. The programming activity is one of the most complex tasks in the management of production because the need to deal with several different types of resources and concurrent activities. Furthermore, the number of solutions grows exponentially in several dimensions, according to the number of tasks, operations or machines, thereby generating a combinatorial nature of the problem. The environment treated in this work each task has the same processing time on any machine. Considering only the restriction independently of the task setup time waiting for processing and the presence of release dates different from zero very practical characteristics in industries. As were found in the literature work that deals of this work environment, even less that used the meta-heuristic Simulated Anneling, so we developed the method to the problem, along with the initial solution their disturbance schemes and the setting of lower bounds for the makespan.
Metaheuristic based on simulated annealing for production schedule in parallel machines with different release dates and time setup
Keywords: Maquinas paralelas; Tempos de setup independentes da sequência; Data de liberação; Simulated Annealing; Parallel machines; Independent setup times the sequence; Release date; Simulated Annealing; ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS